The psychological examination and evaluation of unrelated kidney donors in Israel: a suggested model. Issue 3 (16th March 2023) - Ashkenazi, Tamar; Cohen, Jonathan; Gelman, Daniel; Katvan, Eyal
ABSTRACT: Altruistic organ donors represent a special population when compared to related living donors, requiring appropriate protection and attention regarding informed consent and psychological aspects related to the donation. Following the introduction of the Israeli Transplant Law of 2008, a retrospective study of altruistic donor files revealed that important psycho-diagnostic aspects were not emphasized in the existing guidelines. Thus, a new tool was formulated which incorporated those elements, including assessment of emotional maturity, ego strength, degree of interest in others, reality testing, degree of pressure to donate, anxiety, dysphoric and depressive factors and the ability to function under stress. The study examined 598 cases reviewed by the Central Evaluation Board over the period May 2008 – June 2016. Overall, 23.4% candidates were disqualified of whom 41% were declined on grounds related to mental health. Most of the donors were rejected based on 3–5 elements. Of these, a deficient assessment of reality in ambiguous situations, lack of emotional maturity, and lacking or partial ability to function effectively under stress, were most commonly cited as reasons for rejection. This model allowed the detection of important conditions previously not incorporated into existing guidelines and may serve as a model for other transplantation programs worldwide.